Strongly Maximal Submodules with A Study of Their Influence on Types of Modules - Mohialdeen, Fatima M.; Shihab, Buthyna N. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2022)
Let S be a commutative ring with identity, and A is an S-module. This paper introduced an important concept, namely strongly maximal submodule. Some properties and many results were proved as well as the behavior of that concept with its localization was studied and shown.